- - Taboada R., Paulina (Acta Bioethica, 2000)
By starting with a reflection about the different meanings ascribed to the so-called "right to die with dignity", this work analyses the response given by Palliative Medicine to the end-of-life debate. After reviewing available statistics from Holland -first country in legalizing euthanasia- the author explains the solution that Palliative Medicine has proposed to the issue of "death with dignity". It is necessary to perceive the act of dying as a "human act" in order to understand that response adequately. In this context five moral principles are mentioned, viewed as relevant for safeguarding the ethical dimension of dying. They are: the principles of veracity, therapeutical proportionality, double-effect, prevention and not-abandon. The paper ends with an invitation to change the present medical paradigm, shifting from a medicine controlled by the logic of the "technological imperative" towards a "personalized medicine".